Taqsith Contract: Application And Recognition Of Sales Revenue In Sharia Financial Accounting Reports - Atika Zahra Maulida; Agus Purnomo (Islamic Economics Journal, 2021)
This research is motivated by the existence of financial accounting reports on the recognition of aqad taqsith sales revenue at the Arrahmah Sharia Consumer Cooperative in 2021. This research is a descriptive qualitative study. This type of research (field research). The method used is interviews and accounting documentation in 2021. The subject of this research is the Islamic Consumer Cooperative Arrahmah Banjarmasin Branch. The object of this research is the application of financial accounting reports on the recognition of revenue from the sale of the Taqisth contract (a case study on the Arrahmah Sharia Consumer Cooperative). From the results of this study, the financial accounting reports on the Sarahah sharia consumer cooperative when the installments have not been received by the Sharia cooperative in the recording enter into tough income, but when the installments have been paid the members enter the financial statements as Taqsith income in cash. For its implementation, the Arrahmah Sharia Cooperative uses the Taqsith contract. The Hadith contract itself is in installments or what is nowadays better known as credit